One-step generation of qutrit entanglement via adiabatic passage in cavity quantum electrodynamics - 马宋设 陈美锋 蒋夏萍 (Chinese physics B, 2011)
A scheme is proposed for generating a three-dimensional entangled state for two atoms trapped in a cavity by one step via adiabatic passage. In the scheme, the two atoms are always in ground states and the field mode of the cavity excited is negligible under a certain condition. Therefore, the scheme is very robust against decoherence. Furthermore, it needs neither the exact control of all parameters nor the accurate control of the interaction time. It is shown that qutrit entanglement can be generated with a high fidelity.